Pasir Kucing Ramah Lingkungan dari Pengolahan Limbah Ampas Tahu dengan Teknik Fermentasi Mikroorganisme - Maulia, Refi Ika; Mursyid, Intan Khusnia; Nurhaliza, Resti (Jurnal Pengabdian kepada Masyarakat Cahaya Mandalika (Abdimandalika), 2023)
One of the organic wastes that rots easily is tofu dregs. This waste comes from the remains of processing soybeans into tofu so it rots easily in a short time because it has a fairly high air content. The existence of a tofu industrial center in the Jombang area that is mixed with residential areas causes many environmental pollution problems if it is not managed properly. The impact of waste produced by tofu factories on the environment includes river water turning cloudy and smelling bad, so that river water becomes non-sterile and becomes a nest for disease. The life of living creatures in the river is disturbed. In addition, the unpleasant aroma produced by tofu waste can disrupt the human respiratory system. Based on the problems above, the PKM-K team developed talent, creativity and innovation to create new marketable products made from tofu dregs (Okara). The product that will be developed as a result of the creation is "Environmentally Friendly Cat Sand from Processing Tofu Dregs Waste using Microorganism Fermentation Techniques". The tofu dregs waste processing process uses microorganisms as a way to preserve the waste so that it does not rot quickly.